Evaluación del crecimiento, composición de la canal y calidad de la carne de Búfalos de agua (Bubalus Bubalis) en la Vega de Florencia, San Carlos - López-Sánchez, Leonardo (Instituto Tecnológico de Costa Rica, 2019)
Fisteen buffalos (bubalus bubalis), castrated and weaned as a group most of them when 7 months old were raised in rotational grazing system with an energetic suplementation on daily basis and tropical conditions until 16 months old, moment in which they reached their comertial weight and were send to the harvest plant. During this time, several points were evaluated: Growing rate, reflected by weight, muscle mass and fat cover increase on Longissimus dorsi lumborum muscle; meat yields and carccas composition, done by the deboned and follow up of the industrial process; the bioquimical composition of the meat, setting up the lipid profile and total collagen content; meat tenderness and its respond to wet aging on diferent periods between 2,7,14,21 and 28 days after the animal harvest, several techniques were used as: Myofibrilar Desfragmentation index , measurement of sarcomero lenght and the evaluation of of shear of force (WBSF); and finally the sensorial evaluation of meat, excecuted at 14 days on meat aging by trained panelists. The results showed a rectilinear growing on animals between 9 and 16 months old, with daily gains on weight, all of them positive; and a increase on muscle mass and fat cover. The carcass yield obtained exceeded 53%, more than 85% of this carcass resulted in usable meat and 14% of this was represented by high commercial value cuts. The total collagen obtained represented 1.18% of the sample, while the lipid profile showed a high content of saturated fatty acids in relationship to unsaturated ones. The meat showed an increase in its tenderness as aging days passed, being significantly different at 21 days after harvest (p <0.05), other variables evaluated such as color change and weight and moisture losses were reflected during the time. Finally, the meat was determined as acceptable by the panelists at fourteen days of maturation, being tenderness, juiciness and flavor important aspects of this decision.
Tesis (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Agronomía, 2019.
Keywords: Pastoreo; Bovinos; Inocuidad alimentaria; Ganaderia tropical; Nutrición animal; Asefuramiento de calidad; Carne de búfalo; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Animal production